Low knowledge of newborn danger signs among pregnant women in Papua New Guinea and implications for health seeking behaviour in early infancy - findings from a longitudinal study - Donya Eghrari; Michelle J. L. Scoullar; Alyce N. Wilson; Elizabeth Peach; Arthur Elijah; Pele Melepia; Hadlee SupSup; Lisa M. Vallely; Peter M. Siba; Elissa C. Kennedy; Joshua P. Vogel; Caroline S. E. Homer; et al. (BMC, 2023)
Abstract Background Globally, 2.5 million babies die in the first 28 days of life each year with most of these deaths occurring in low- and middle-income countries. Early recognition of newborn danger signs is important in prompting timely care seeking behaviour. Little is known about women's knowledge of newborn danger signs in Papua New Guinea. This study aims to assess this knowledge gap among a cohort of women in East New Britain Province. Methods This study assessed knowledge of newborn danger signs (as defined by the World Health Organization) at three time points from a prospective cohort study of women in East New Britain Province, factors associated with knowledge of danger signs after childbirth were assessed using logistic regression. This study includes quantitative and qualitative interview data from 699 pregnant women enrolled at their first antenatal clinic visit, followed up after childbirth (n = 638) and again at one-month post-partum (n = 599). Results Knowledge of newborn danger signs was very low. Among the 638 women, only 9.4% knew three newborn danger signs after childbirth and only one knew all four essential danger signs defined by Johns Hopkins University 'Birth Preparedness and Complication Readiness' Index. Higher knowledge scores were associated with higher gravidity, income level, partner involvement in antenatal care, and education. Conclusion Low levels of knowledge of newborn danger signs among pregnant women are a potential obstacle to timely care-seeking in rural Papua New Guinea. Antenatal and postnatal education, and policies that support enhanced education and decision-making powers for women and their families, are urgently needed.